Peningkatan Kinerja Guru Melalui Musyawarah Guru Mata Pelajaran ( MGMP ) Bahasa Indonesia di SMPN 1 Labuhan Haji Tahun 2016/2017 - Islahuddin, Islahuddin (Universitas Hamzanwadi, 2018)
The purpose of this study was to improve the performance of Indonesian language teachers in (1) learning planning, (2) the application of learning strategies, (3) classroom practice, and the implementation of MGMP learning (Subject Teacher Consultation) at Labuhan Haji 1 Junior High School in East Lombok Regency. The approach used is a quantitative approach to the type of action. The object of this study were 15 Indonesian Language teachers, 15 Indonesian Language teachers who were members of the Central Rayon Indonesian Language MGMP whose activities were centered at Labuhan Haji 1 Junior High School in East Lombok Regency. The data instruments used were knowledge tests, analysis, interviews, and portfolios. Hypothesis testing is done by looking at the improvement in the performance of the teacher's curriculum. The average score of the work score increased from 53.2 to reach 68.9 in cycle II. Because the performance score has reached 68.9 (rounded to 70), the alternative Hypothesis (Ha) which states the implementation of MGMP at Labuhan Haji 1 Public Middle School can improve teacher performance in learning planning, classroom management, and learning evaluation. The results of this study are that the implementation of MGMP in Labuhan Haji Middle School 1 can improve the performance of Indonesian Language teachers in learning planning, implementation of learning strategies, and learning. Thus the MGMP provisions that succeed in implementing the principles of human price management can improve the performance of Indonesian Language teachers in learning. Therefore, education teachers, school principals, and education supervisors are empowering the MGMP MGMP that exists mainly in schools because it can improve teacher professionalism.Keywords: teacher performance; MGMP; Indonesian language.